Cutis Verticis Gyrata Differential Diagnosis: Clinical Case - Tatiana S. Belysheva; Ekaterina E. Zelenova; Tatiana A. Gassan; Eduard T. Ambarchyan; Malika I. Denieva; Yana V. Vishnevskaya; Tatiana V. Nasedkina; Nikolay N. Murashkin (Вопросы современной педиатрии, 2024)
Background. Cutis verticis gyrata is rare benign scalp disorder characterized by excessive skin and subcutaneous tissue proliferation and hypertrophy. Nowadays, there are three forms of this disease with various developmental mechanisms and associated manifestations. Clinical case description. This article presents the patient admitted with diagnosis and clinical picture of pachydermia, who underwent surgical excision of scalp abnormal tissues. However, the diagnosis of giant congenital melanocytic nevus was established according to the results of clinical examination. Later it was confirmed by histological and immunohistological studies. Moreover, pathogenic variants in the NRAS gene were not revealed. Conclusion. This case demonstrates the complexity of differential diagnosis of pachydermia that leads to careful examination of patients with morphogenetic studies of affected tissues samples.